2019 18th European Control Conference (ECC) 2019
DOI: 10.23919/ecc.2019.8796166
|View full text |Cite
|
Sign up to set email alerts
|

Sliding mode control of a differential-drive mobile robot following a path

Abstract: This paper presents a control algorithm for a differential-drive robot following a path. The main contributions are: a new control formulation that does not require the robot global position, and a nonlinear controller based on the sliding mode control approach that guarantees stability in both forward and backward motion. Numerical simulations are provided to validate the proposed algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is shown that the formation tracking error converge to a neighborhood of the origin in a fixed time. In [10], a first-order sliding-mode controller is presented for a differential-drive robot following a path. The proposed approach is able to ensure local asymptotic stability of the path tracking in terms of the Frénet-Serret frame.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the formation tracking error converge to a neighborhood of the origin in a fixed time. In [10], a first-order sliding-mode controller is presented for a differential-drive robot following a path. The proposed approach is able to ensure local asymptotic stability of the path tracking in terms of the Frénet-Serret frame.…”
Section: Introductionmentioning
confidence: 99%
“…After designing the reference trajectory, an appropriate control strategy is required to track the trajectory. Fuzzy logics [2], PID tuning methods [3], sliding mode control [4], and a combination of them [5] are among common control strategies.…”
Section: Introductionmentioning
confidence: 99%